Dampak Work From Home Selama Pandemi Covid-19 terhadap Kondisi Fisiologis dan Perilaku Komunikasi - Putra Fajar, Dewanto (Jurnal Komunikasi Nusantara, 2020)
The Covid-19 pandemic brought a variety of major changes to human social life throughout the world, including in Indonesia. The situation requires the government to impose work activities from home or known as WFH (working from home). Such a situation changes the behavior of human communication, which at first more often uses direct interaction directly, now changes to use digital media, thus creating a kind of social shock in the communication process. Furthermore, such changes take place over an uncertain period of time, so it is possible to raise a number of problems, related to personal conditions, which then affect communication behavior. This article seeks to find out the effect of applying work from home policies on physiology to communication behavior, using qualitative methods with a participatory approach, by observing changes in physiological conditions and individual communication behavior. Thus, this article is expected to reveal the hidden impact of the application of work from home, on physiological conditions and communication behavior. Keywords: Covid-19, Work from home, Communication behavior, Physiology, Communibiology